2003
DOI: 10.1002/ajmg.a.20343
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of UBE3A and MECP2 in Angelman syndrome (AS) and patients with features of AS

Abstract: Angelman syndrome (AS) is an imprinted neurobehavioral disorder characterized by mental retardation, absent speech, excessive laughter, seizures, ataxia, and a characteristic EEG pattern. Classical lesions, including deletion, paternal disomy, or epigenetic mutation, are confirmatory of AS diagnoses in 80% of cases. Loss-of-function mutations of the UBE3A gene have been identified in approximately 8% of AS cases, failing to account for the remaining patient population, and there appears to be a higher prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
1
17
0
2
Order By: Relevance
“…As the only inherited multiple nucleotide deletion (case NS 27) originated post-zygotically in the mother, a mosaic carrier, this case should be excluded from the analysis, resulting in a significant association between inheritance and type of mutation (P ¼ 0.02; Fisher's exact test). In order to test this hypothesis, we reviewed all the mutations published in the literature taking into account their inheritance status and excluding mosaicism [Kishino et al, 1997;Matsuura et al, 1997;Fung et al, 1998;Malzac et al, 1998;Tsai et al, 1998;Baumer et al, 1999;Fang et al, 1999;Russo et al, 1999Russo et al, , 2000Hitchins et al, 2004;Rapakko et al, 2004;Hosoki et al, 2005;Bonaglia et al, 2007]. We found that the proportion of multiple nucleotide deletions and insertions occurring de novo (28/46 ¼ 0.61) almost doubled that of the single nucleotide substitutions (7/22 ¼ 0.32), and this difference was significant (P ¼ 0.015).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As the only inherited multiple nucleotide deletion (case NS 27) originated post-zygotically in the mother, a mosaic carrier, this case should be excluded from the analysis, resulting in a significant association between inheritance and type of mutation (P ¼ 0.02; Fisher's exact test). In order to test this hypothesis, we reviewed all the mutations published in the literature taking into account their inheritance status and excluding mosaicism [Kishino et al, 1997;Matsuura et al, 1997;Fung et al, 1998;Malzac et al, 1998;Tsai et al, 1998;Baumer et al, 1999;Fang et al, 1999;Russo et al, 1999Russo et al, , 2000Hitchins et al, 2004;Rapakko et al, 2004;Hosoki et al, 2005;Bonaglia et al, 2007]. We found that the proportion of multiple nucleotide deletions and insertions occurring de novo (28/46 ¼ 0.61) almost doubled that of the single nucleotide substitutions (7/22 ¼ 0.32), and this difference was significant (P ¼ 0.015).…”
Section: Discussionmentioning
confidence: 95%
“…This high proportion of novel mutations suggests that the variability of mutational changes causing AS will increase as new cases are described. Nevertheless, multiple nucleotide deletions or insertions can be recurrent, as 2507_2510del4 for example, which has been found in most patients series [Fang et al, 1999;Hitchins et al, 2004;Rapakko et al, 2004;present work] and the distribution of mutations along the coding sequence does not seem to be uniformly distributed. The finding of some recurrent mutations may be a clue for the existence of some mutational hotspots in the UBE3A gene sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally described as a transcriptional repressor of methylated genes, new roles for MeCP2 in chromatin organization and alternative splicing have recently emerged (Horike et al, 2005;Yaui et al, 2007;Young et al, 2005). Angelman syndrome is an imprinted disorder caused by maternal 15q11-13 deficiency or mutation of the ubiquitin protein ligase E3 gene, UBE3A, that also shares features with both Rett syndrome (RTT) and autism (Hitchins et al, 2004;Lalande and Calciano, 2007;Philippart, 2001;Watson et al, 2001). The demonstration of MeCP2 as a regulator of both UBE3A (the Angelman gene) and GABRB3 (encoding a GABA A receptor subunit) expression within 15q11-13 has revealed some interesting insights into the genetic and epigenetic pathways common to all three disorders Samaco et al, 2005).…”
Section: Epigenetic Influences On Autism Risk: a Role For Gaba A mentioning
confidence: 99%
“…Laurent V reported the frequency of MECP2 mutations causing mental retardation in males was estimated between 1.3% and 1.7% (Villard, 2007). MECP2 mutations in females often cause classical or variant phenotypes of RTT, while in males more severe phenotypes, including moderate to severe MR and congenital encephalopathy or early dearth, occur (Hitchins et al, 2004). …”
Section: Introductionmentioning
confidence: 99%